PENGARUH METODE AKTIF TIPE TEAM QUIZ BERBANTUAN QUESTION CARD TERHADAP HASIL BELAJAR - Putri, Septiyani Dwi; Subroto, Tjahyo; Sunarto, Wisnu (Chemistry in Education, 2013)
This research is done to findout the effect of the using of active methods team quiz with question card towards the students’ achievement of the eleventh grade student about buffer solution and hydrolysis of SMA Muhammadiyah Wonosobo. The population is the eleventh grade students of natural science. Sample was conducted by cluster random sampling technique, obtained a XI IPA 2 as the experimental class get the learning used active method team quiz with question card and the XI IPA 3 as a control class get the learning used conventional method . To collect the data the writer used documentation, test, observation and questionnaires. The result of the research show that the chemist learning used active method team quiz with question card affects toward the students’ chemist achievement of the eleventh grade students of natural science about buffer solution and hydrolysis of SMA Muhammadiyah Wonosobo. The data analysis biserial correlation technique show coeficient correlation (rb) is 0.461, this fact show coefficient of the determination (KD) is 21.25%. From the analysis can be concluded that the using of active method team quiz with question card effect towards the students’ achievement buffer solution and hydrolysis with the contribution 21,25%.